Feline Papillomatosis - Herman Egberink; Katrin Hartmann; Ralf Mueller; Maria Grazia Pennisi; Sándor Belák; Séverine Tasker; Karin Möstl; Diane D. Addie; Corine Boucraut-Baralon; Tadeusz Frymus; Regina Hofmann-Lehmann; Fulvio Marsilio; et al. (Viruses)
Different types of feline papillomaviruses (PVs) are associated with a variety of skin lesions and neoplasia, such as papillomas and cell carcinomas, but the virus can also be found in healthy skin. In this review, the European Advisory Board on Cat Diseases (ABCD), a scientifically independent board of veterinary experts on feline infectious diseases from 11 European Countries, discusses the current knowledge of feline PV infections. Cats most likely become infected through lesions or abrasions of the skin. Most PV infections remain asymptomatic. Besides cat-specific PVs, DNA sequences most closely related to human and bovine PVs have been detected in feline skin lesions. Diagnosis is supported by the histological detection of PV-induced cell changes and intralesional detection of viral antigen (immunostaining) or viral DNA (in situ hybridization). Immunostaining of p16CDKN2A protein (p16) can be performed as a proxy marker for PV-induced neoplasms. There is no specific treatment for PV-induced skin lesions. Spontaneous regression commonly occurs. In the case of invasive squamous cell carcinoma (ISCC), complete excision should be considered, if possible.